2016
DOI: 10.1021/acs.biochem.6b01044
|View full text |Cite
|
Sign up to set email alerts
|

Allostery and Hysteresis Are Coupled in Human UDP-Glucose Dehydrogenase

Abstract: Human UDP-glucose dehydrogenase (hUGDH) is regulated by an atypical allosteric mechanism in which the feedback inhibitor UDP-xylose (UDP-Xyl) competes with substrate for the active site. Binding of UDP-Xyl triggers the T131-Loop/α6 allosteric switch, which converts the hexameric structure of hUGDH into an inactive, horseshoe-shaped complex (EΩ). This allosteric transition buries residue A136 in the protein core to produce a subunit interface that favors the EΩ structure. Here we use a methionine substitution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(58 citation statements)
references
References 42 publications
(187 reference statements)
5
53
0
Order By: Relevance
“…18, 19, 23 This hypothesis is supported by a previous study that showed trapping the allosteric switch in the active conformation abolishes hysteresis. 23 The remarkable plasticity exhibited by the hUGDH protein core likely originates from large cavities and deep surface pockets (declivities) near the allosteric switch (Figure 1D). 15 Here, we have examined how the flexibility of the hUGDH protein core contributes to both hysteresis and allostery.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…18, 19, 23 This hypothesis is supported by a previous study that showed trapping the allosteric switch in the active conformation abolishes hysteresis. 23 The remarkable plasticity exhibited by the hUGDH protein core likely originates from large cavities and deep surface pockets (declivities) near the allosteric switch (Figure 1D). 15 Here, we have examined how the flexibility of the hUGDH protein core contributes to both hysteresis and allostery.…”
Section: Introductionsupporting
confidence: 70%
“…The NAD + saturation curves of hUGDH A104L are hyperbolic (Hill=1), with a K M of 48±3 μM (Figure 5C, Table 3). In contrast, the NAD + saturation curves of native hUGDH are known to display negative cooperativity 18, 19, 23 (Figure 5D Table 3). Earlier work showed that UDP-Glc binding induces an asymmetry that results in a mixture of high and low affinity NAD + binding sites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations